Food safety and nutrition for low-income urbanites: exploring a social justice dilemma in consumption policy - Wertheim-Heck, Sigrid C.O.; Raneri, Jessica Evelyn; Oosterveer, P. (SAGE Publications, 2019)
Equitable access to healthy food is a critical challenge in urban Asia. Food safety governance promotes modern supermarkets over more traditional markets, but supermarkets are associated with unequal access to food. This study investigates how retail policies driven by food safety impact the diets of the urban poor in Hanoi, Vietnam. We do this by linking food retail infrastructures with the food shopping practices and measured dietary intake of 400 women. Our results reveal sub-optimal dietary diversity and reliance on foods sourced through traditional markets, which do not provide formal food safety guarantees. Modern channels supply formal food safety guarantees, but are mainly frequented for purchasing ultra-processed foods. The paper uncovers a conflicting duality governing food security and suggests that the public responsibility for ensuring access of the poor to nutritious and safe foods requires a more diverse retail policy approach